Results of thermo-magnetic analysis of Cretaceous deposits of the Lagich section (Vandam tectonic zone, South slope of the Greater Caucasus, Azerbaijan) - Z.A. Novruzov; M.I. Isayeva; T.D. Garayeva; A.A. Bagirova (Геофизический журнал, 2017)
The magnetic study of a tuffbreccia, tuffaceous sandstone, clay rocks, chalky clays, marls and silicides of Cretaceous deposits (the Albian Age, the Cenomanian Age and Turonian—Cognacian Age) the Lagich section of the Vandam tectonic zone of Greater Caucasus (Azerbaijan) has been carried out. For thermomagnetic analysis the magnetic parameter of saturation remanence Jrs is used. The magnetic and mineralogical structure of carriers of natural remanent magnetization is determined by the shape of curves and by blocking temperature Tb of the studied samples. As a result of the analysis of curves of demagnetization of Jrsit has been established that the main carriers of natural remanent magnetization of the studied samples in the Lagich section are magnetite and hematite. On several samples during thermodemagnetization of Jrs the curves have displayed the presence of pyrrhotite (greygit). But on mineralogical researches of department of "Analytical center" of Institute of Geology of National Academy of Sciences of Azerbaijdan presence of pyrrhotite (greygit) in the studied samples hasn't been revealed. In Cretaceous deposits (the Albian Age, the Cenomanian Age and Turonian—Congnacian Age) however availability of magnetite and hematite are checked out by department of "Analytical center" in the Lagich section